Study of the transient release of water vapor from a fuel bed of wet biomass in a reciprocating-grate furnace. Issue 4 (August 2019) - Razmjoo, Narges; Hermansson, Sven; Morgalla, Mario; Strand, Michael
Abstract: The present study investigates how sudden changes in fuel moisture affected the combustion characteristics of the fuel bed in a 4-MW reciprocating-grate furnace. The moisture content of the fuel fed to the furnace was monitored online using a near-infrared spectroscopy device, and the water vapor concentration in the flue gas was measured continuously. To obtain experimental data on fuel-bed conditions, the temperature and gas composition in the bed were measured using a probe. A simplified drying model was developed using the measured gas composition values as inputs. The model was then used to estimate the drying rate and to simulate the extent of the drying zone along the grate. Measurements indicated that a change in the moisture content of the fuel fed to the furnace was detected as a change in water vapor concentration in the flue gas with a delay of about 2 h. The model predicted that a portion of wet fuel would need about 2 h to become dry, in line with the measured time delay of the water vapor concentration change in the flue gas. Overall, there was good alignment between the measured and simulated results, supporting the validity of the model and the assumed mechanisms. Highlights: Fuel moisture and water vapor concentration in flue gas were measured continuously. Temperature and gas concentration measured inside the fuel bed of a grate boiler. A simplified drying model was developed to estimate the extent of drying zone. Change in fuel moisture was detected in flue gas with a delay of about 2 h.